Financial performance analysis of GSK with a comparison to few of the leading pharmaceutical companies of Bangladesh - Billah, Mahin Mutasim (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.